The measurement of large antennas with cosmic radio sources - Baars, J. (IEEE transactions on antennas and propagation, 1973)
Strong cosmic radio sources provide a constant broadband and accurately positioned test transmitter for measurements of large antennas. Some sources have their flux density determined absolutely and can be used to calibrate the antenna gain. This paper presents up-to-date data on the radio sources which are useful for antenna measurements. The measurement of pointing and focusing corrections is discussed. The main part of the paper is concerned with the derivation of major antenna parameters such as aperture and beam efficiency, beam solid angle, sidelobe levels, error pattern characteristics from measurements on radio sources. The effects of a finite angular source size are discussed, and it is shown how measurements on sources of different size increase the information on the derived antenna parameters. The methods to measure very weak sidelobes are treated and the external factors, solar and galactic radiations influence of the earth and atmosphere, which might limit the accuracy of the measurement are described. The paper takes a practical approach to the subject and contains graphs with numerical data.